2018
DOI: 10.18203/2320-1770.ijrcog20180201
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of oral nifedipine and intravenous labetalol in control of acute hypertension in severe pre-eclampsia and eclampsia

Abstract: Background: This study was conducted to compare oral Nifedipine and intravenous Labetalol in control of acute hypertension in severe pre-eclampsia and eclampsia. This study was observational study with 80 sample size in which 40 sample size treated with intravenous Labetalol and other 40 sample size treated with oral Nifedipine. The maternal and perinatal outcome in two groups sample size with oral Nifedipine and intravenous Labetalol compared and found that nevertheless these results do establish oral Nifedip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…17 Vermillion et al, and Gavit Y et al, in their studies reported 100% success rate to achieve the target blood pressure with both drugs. 12,18 In the present study, it is evident that volume of urine output, in patients treated with oral nifedipine was significantly higher at the end of the first hour of treatment in comparison to intravenous labetalol; significantly increased urine output in nifedipine group persisted at least till 24 hours after the commencement of the treatment. Barton J et al, and Dhali B et al in their studies reported similar significant increase in urine output in nifedipine group.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…17 Vermillion et al, and Gavit Y et al, in their studies reported 100% success rate to achieve the target blood pressure with both drugs. 12,18 In the present study, it is evident that volume of urine output, in patients treated with oral nifedipine was significantly higher at the end of the first hour of treatment in comparison to intravenous labetalol; significantly increased urine output in nifedipine group persisted at least till 24 hours after the commencement of the treatment. Barton J et al, and Dhali B et al in their studies reported similar significant increase in urine output in nifedipine group.…”
Section: Resultssupporting
confidence: 45%
“…Intergroup difference of adverse effects was not statistically significant. [16][17][18] Oral nifedipine group also required less number of doses to achieve the target BP in comparison to IV labetalol (1.75±0.840 vs. 2.18±0.83), p= 0.024. However, both the drugs were successful in achieving the target blood pressure within the study period and so no patients required crossover treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Similar trials conducted by Raheem et al, Shekhar et al, Anjuman et al and Yogita et al showed that BP control was controlled significantly earlier in patients who were given Nifedipine as compared to labetalol and they required less number of doses. 7 , 10 - 12 Lakhshami et al declared labetalol superior regarding earlier control of BP while Shi DD et al reported both achieved BP control at same time with two doses in both groups. 13 , 14 The difference results in various trials may be related to the smaller number of participants in each group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, average gestation was 34.8±2.73 weeks in labetalol Group-And 35.2±2.48 weeks in patients given Nifidepine with average birth weight of 2.2±0.41kg and 2.3±0.38 kg respectively (p>0.05) This is in contrast to studies reported by Raheem et al and Yogita et al where majority babies delivered at gestational age of 37-39 weeks. 5 , 12 The reason may be that quite a lot of our patients were unbooked and were not taking any antenatal care. Regular antenatal care has key role to play in BP control and hence prolongation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational age in group I patients was 36-37 weeks seen 4 in group I and 5 in group II, 37-38 weeks seen 10 in group I and 9 in group II, 38-39 weeks 11 in group I and 10 in group II and >39 weeks 5 in group I and 6 in group II. Gavit et al, [8] compared oral Nifedipine and intravenous Labetalol in control of acute hypertension in severe preeclampsia and eclampsia. In this study, 40 sample size treated with intravenous Labetalol and other 40 sample size treated with oral Nifedipine.…”
Section: Discussionmentioning
confidence: 99%